Tumor Necrosis Factor-α Variations in Patients With Major Depressive Disorder Before and After Antidepressant Treatment - Yao, Lin; Pan, LiHong; Qian, Min; Sun, Wei; Gu, ChunHong; Chen, LiangHu; Tang, XiaoChen; Hu, YeGang; Xu, LiHua; Wei, YanYan; Hui, Li; Liu, XiaoHua; et al. (Frontiers in Psychiatry, 2020)
Tumor necrosis factor-α (TNF-α) had been identified as a key pro-inflammatory cytokine in the pathophysiology of major depressive disorder (MDD) and the mechanism of antidepressant treatment. The primary aim of the present study was to examine the serum TNF-α levels in Chinese inpatients with MDD during the acute phase and to explore the changes in TNF-α levels after effective clinical treatment. Fifty-seven consecutive inpatients with MDD and 30 healthy controls were recruited. The serum TNF-α levels were detected using ELISA. Symptoms of depression were evaluated using the 24-item Hamilton Rating Scale for Depression (HAM-D-24). TNF-α levels and HAM-D-24 scores were assessed at baseline and after 2 and 12 weeks of follow-up. The serum TNF-α levels were higher in the MDD group than in the control group. After 2 and 12 weeks of antidepressant treatment, there were significant improvements in the patients’ symptoms and significant decreases in the TNF-α levels. The baseline TNF-α levels significantly correlated with the decreased HAM-D-24 scores, particularly for the depressive symptoms of anxiety/somatization and weight loss. The present findings indicate that depression is accompanied by activation of TNF-α, which also has a predictive value for the antidepressant treatment response in patients with MDD.